An amplicon-based approach for full-genome characterization of HPV16 - Isabelle Malet; Inès Draa; Valentin Leducq; Fanny Vuong; Pascale Bonnafous; Anne-Geneviève Marcelin; Vincent Calvez; Aude Jary (Microbiology Spectrum)
ABSTRACT Among the various genotypes of the human papillomavirus (HPV), the HPV16 genotype is the most oncogenic by far, and some (sub)lineages may be associated with an increased risk of cancer. Thus, characterizing the full genome is important to understand the link between the HPV16 genome variability and its transforming role. We set up a multiplex PCR approach combined with Oxford Nanopore Technologies for the HPV16 full-genome characterization. The primers were designed with PrimalScheme, and the optimization of the monoplex/multiplex PCR was performed on SiHa cells. After library preparation, the sequencing was performed on a GridION sequencing device to determine the sensitivity, the specificity, and the performance of the method. Fourteen primer pairs were selected to span the full genome. With the monoplex PCR, 12 primer pairs showed good amplification, while a double concentration of two primers was required to improve the amplification. We then performed a multiplex PCR approach by generating two pools comprising non-overlapping primer pairs. The multiplex PCR showed good sensitivity, allowing the amplification of HPV16 with a Ct value below 27 and providing a coverage greater than 99.9% and a sequencing depth greater than 100×. In addition, the specificity of the method was validated by the absence of amplification of other high-risk HPV genotypes compared with HPV16. We set up an amplicon-based approach to characterize the full genome and diversity of the HPV16 (sub)lineages. This approach shows good sensibility and specificity with limited cost, opening new perspectives in the field of whole-genome HPV sequencing.IMPORTANCEHPV16 is by far the most oncogenic genotype, so characterizing the genetic variability of its genome is important to better understand the link with its transforming role. We developed an amplicon-based approach combined with Oxford Nanopore Technologies next-generation sequencing to overlap the HPV16 genome, which is easy to implement in the laboratory and inexpensive in the field.